Biographical research in the context of interdisciplinary synthesis - G. V. Varganova (Библиосфера, 2018)
The article determines the role of biographical research in strengthening the scientific status of library-information science. The results of biographical research allows understanding the role and mission of the library science in frameworks of the world scientific view; determining its interrelations and cooperation with different disciplines; showing the historical dynamics in research topics, scientific ideals and standards, main mechanisms for obtaining new knowledge and possibilities for its application in practical activity in the library-information sphere. Biographical research permit to highlight the contribution of individual researchers and practitioners in developing the library-information science in different historical periods. Biographical researches are encouraged by national library associations and library schools as an instrument, which helps to predict future trends in the library-information science and practice and to overcome risks in their development at the national level. The main obstacles in carrying out biographical research are the following: the information science dynamics, the lack of financial resources and professional support, electivity of the library history course in library higher schools curricula, quantitative methodology non-possession, mistrust to results of biographical research. Interdisciplinary synthesis based on overcoming disciplinary boundaries allows applying the integral potentiality of different disciplines successfully. It is essentially the main instrument for planning research, identifying main problems and sub-problems, constructing and evaluating hypothesis and sources, designing databases, processing results, developing theoretical frameworks. The interdisciplinary synthesis helps to control main study phases of biographical research, particularly analysis and interpretation of data. It predetermines the necessity of using complementary scientific methods relevant to an investigating problem. The interdisciplinary and methodological synthesis should be considered as the basic factors for obtaining objectivity, validity and reliability of biographical research results.